2015
DOI: 10.4137/pmc.s13214
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Second-Harmonic Generation Imaging Microscopy in Ovarian and Breast Cancer

Abstract: In this perspective, we discuss how the nonlinear optical technique of second-harmonic generation (SHG) microscopy has been used to greatly enhance our understanding of the tumor microenvironment (TME) of breast and ovarian cancer. Striking changes in collagen architecture are associated with these epithelial cancers, and SHG can image these changes with great sensitivity and specificity with submicrometer resolution. This information has not historically been exploited by pathologists but has the potential to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 73 publications
(147 reference statements)
1
63
0
Order By: Relevance
“…Varying the initial collagen concentration regulated porosity, fiber width and fiber length and the microscale mechanics varied as a function of polymerization temperature (Figure 1). We found that pore area, fiber width, and fiber length decreased with increasing polymerization temperature and achieved distributions of fiber widths, lengths and porosity comparable to those described by others (Figure 1)(Bredfeldt, Liu, Conklin, et al, 2014; Bredfeldt, Liu, Pehlke, et al, 2014; Khanna et al, 2015; Tilbury & Campagnola, 2015). …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Varying the initial collagen concentration regulated porosity, fiber width and fiber length and the microscale mechanics varied as a function of polymerization temperature (Figure 1). We found that pore area, fiber width, and fiber length decreased with increasing polymerization temperature and achieved distributions of fiber widths, lengths and porosity comparable to those described by others (Figure 1)(Bredfeldt, Liu, Conklin, et al, 2014; Bredfeldt, Liu, Pehlke, et al, 2014; Khanna et al, 2015; Tilbury & Campagnola, 2015). …”
Section: Discussionsupporting
confidence: 89%
“…Using confocal reflection microscopy we achieved ~250 nm optical resolution (lateral). The ctFIRE algorithm employed here has been used extensively to quantify fiber properties(Bredfeldt, Liu, Conklin, et al, 2014; Bredfeldt, Liu, Pehlke, et al, 2014; Khanna, Wells, PurĂ©, & Volk, 2015; Tilbury & Campagnola, 2015). Varying the initial collagen concentration regulated porosity, fiber width and fiber length and the microscale mechanics varied as a function of polymerization temperature (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…These new materials such as 3‐methyl‐4‐methoxy‐4â€Č‐nitrostilbene self‐assembled into hexagonal microprisms and 2,7‐diphenyl‐9 H‐fluoren‐9‐one microfibers have been already introduced as effective nonlinear photonic waveguides. As shown in the former sections, both biological fibers and bioinspired peptide nanostructures FF‐PNT and FFF‐PNTp exhibit nonlinear second order optical response, and thus make them possible to guide second harmonic frequency wave in their noncentrosymmetric clad both for medical diagnostics and device applications . To test their waveguiding property, vertically aligned FF‐PNT were fabricated by the breath figure method .…”
Section: Peptide Integrated Opticsmentioning
confidence: 99%
“…In his group's work, stromal remodeling was investigated along the continuum of ovarian pathology from normal stroma, to benign tumors, to low-and high-grade tumors using a biomedical engineering approach. 11,12 Interestingly, stromal characteristics are unique among the pathology types, and characterization of the stromal architecture can predict the subtype of epithelial cell pathology. In addition to tumor cells impacting stromal behavior, multiple investigators reported on the effects of stromalderived signals on tumor cells.…”
Section: Role Of Stromal Cells In the Tumor Microenvironmentmentioning
confidence: 99%